Telomere Attrition With Concomitant hTERT Overexpression Involved in the Progression of Gastric Cancer May Have Prognostic and Clinical Implications in High-Risk Population Group From North India - Mushtaq, Ifra; Bhat, Gh Rasool; Rah, Bilal; Besina, Syed; Zahoor, Sheikh; Wani, Muneer A.; Shah, Mubashir A.; Bashir, Sadaf; Farooq, Muzamil; Rather, Rafiq A.; Afroze, Dil (Frontiers in Oncology, 2022)
Genetic instabilities exacerbated by the dysfunction of telomeres can lead to the development of cancer. Nearly 90% of all human malignancies are linked with telomere dysregulation and overexpression of telomerase, an enzyme that catalyzes the synthesis of telomeric DNA repeats at the ends of chromosomes. The burden of gastric cancer continues to inflict a deterring impact on the global health scenario, accounting for over one million new cases in 2020. The disease is asymptomatic in its early stages of progression, which is attributed to the poor prognosis and overall surge in mortality rate worldwide. Exploiting telomere physiology can provide extensive mechanistic insight into telomere-associated gastric cancer progression and its use as a target in a variety of therapeutic interventions. In this study, we aimed to evaluate the clinical implications of c-Myc, human telomerase reverse transcriptase (hTERT) expression, and telomere length in patients with gastric cancer. A total of 57 gastric cancer cases and adjacent controls were included in the study. RT-PCR and immunohistochemistry were used to assess the expression levels of c-Myc and hTERT. The relative telomere length was measured by MMQPCR using the Cawthon method. Our results indicated that the shorter telomere and increased hTERT expression were associated with gastric cancer progression. The study also highlighted the role of short telomeres and increased expression of hTERT in gastric cancer progression and its association with various etiological risk factors, transcriptional activators, and overall survival among the ethnic Kashmiri population of North India.